(untitled) (Nordic Journal of African Studies, 2011)
This paper examines The High Tone Syllable (HTS) in Arigidi. The HTS, an element which occurs between the subject NP and the VP in declarative sentences has only been found in Yorùbá and some of its dialects. In Arigidi, the HTS usually occurs between the subject and the verb phrase in declarative sentences too. This paper revealed that the HTS in Arigidi regularly replaces the last syllable of the preceding NP whenever the NP shows up in that position. This paper also affirms that the HTS is a tense and aspectual marker which indicates past/present and completed actions in Arigidi.